The Influence of Brand Image and Online Customer Reviews on Online Fashion Product Purchase Decisions on Shopee among Students of the Faculty of Economics, Santo Thomas Catholic University, Medan - Hezron Apriadi Situmorang; Riza Fanny Meutia; Adelina Lubis; Fitriani Tobing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of Brand Image and Online Customer Reviews on Online Fashion Product Purchase Decisions on Shopee. The type of research used is associative research with a quantitative approach. The population in this study was 380 people, determined by a purposive sampling technique, with a sample size of 79 people using the Slovin formula. Data collection was carried out through questionnaires and data processing using SPSS software. From partial testing, the T test showed that t count (2.644) > t table (2.011), with a significance level of 0.000 > 0.05, proving that brand image has a positive and significant effect on purchasing decisions. And in the online customer review variable, the t count value (4.441) > t table (2.011) with a significance level of 0.000 > 0.05, proving that online customer reviews have a positive and significant effect on purchasing decisions. F test shows that F count is 67.177 > 3.11 (F table), so it can be concluded that simultaneously brand image and online customer review variables have a positive and significant effect on purchasing decisions. From the discussion of multiple linear regression, Y = 9.005 + 0.448X1 + 0.495X2. It can be concluded that brand image and online customer reviews have a positive and significant effect on purchasing decisions for fashion products among students of the Faculty of Economics, Santo Thomas Catholic University, Medan. The coefficient of determination (R2) of 0.799 means that purchasing decisions can be explained by brand image and online customer reviews by 63.9% while another 36.1% can be explained by other factors not examined in this study.